2010
DOI: 10.1598/rt.64.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Digital Readers: The Next Chapter in E‐Book Reading and Response

Abstract: The basic features of digital reading devices (such as the Amazon Kindle) are described in this article. The author also considers how such devices can advance e‐book readership among primary students by offering new avenues for accessing and interacting with a wide array of texts. Rooted in the transactional theory of reader response and a new literacies perspective, this case study examines the reading and response behaviors of two second‐grade girls as they read a book on a digital reading device. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 4 publications
6
92
1
9
Order By: Relevance
“…For example, in a US study of younger children's "involvement with and response to digital readers" [43] occurred in a site where their classroom teacher had actively positioned children in advance, to produce a favorable response: "Mrs. Miles, the classroom teacher, is an avid proponent of technology integration who encouraged her 17 second graders to read online texts, blog about their reading experiences, and engage in online literature discussions."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a US study of younger children's "involvement with and response to digital readers" [43] occurred in a site where their classroom teacher had actively positioned children in advance, to produce a favorable response: "Mrs. Miles, the classroom teacher, is an avid proponent of technology integration who encouraged her 17 second graders to read online texts, blog about their reading experiences, and engage in online literature discussions."…”
Section: Discussionmentioning
confidence: 99%
“…Miles, the classroom teacher, is an avid proponent of technology integration who encouraged her 17 second graders to read online texts, blog about their reading experiences, and engage in online literature discussions." [43] It would appear that in some cases, the research appearing in peer-reviewed international literacy and education journals in this area may lack sufficient objectivity. The degree of enthusiastic advocacy from educators around eBook use, whatever the root causes, has led to issues with research design, with one of the key issues that impacts on the validity of the studies in this area being the partial and often vested interests present in those conducting the study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Larson (2010) reported on how second-grade students read with a Kindle e-reader, making use of features such as adjusting the font size, listening to parts of the story by activating the text-to-speech feature, highlighting key passages or vocabulary, using the built-in dictionary, searching for keywords or phrases within the book, and adding annotations to the text in response to what they were reading.…”
Section: Digital Tools To Support Reading Comprehensionmentioning
confidence: 99%
“…Kindle e-reader (Larson, 2010) 1) Increased opportunities to engage with and manipulate text through the electronic tools and features. 2) Affords the reader greater control.…”
Section: ) Students Need Time To Become Familiar With the Touchscreementioning
confidence: 99%
“…The ability to search across an entire book or to look up words in an integrated dictionary are commonly cited advantages. Preliminary studies of the way children use ebook devices have suggested that search and dictionary features are useful in establishing and developing literacy but that their utility varies somewhat in relation to the fluency of the reader (Larson, 2010): the more fluent the reader, the less need for the dictionary. Schools in England have begun to take advantage of the multimedia affordances of ebook devices to support students navigating schoolwork in a second language: English language written texts are supported by supplementary audio support in Polish (Morrison, 2009).…”
Section: Ebook Devices and Knowledge Workersmentioning
confidence: 99%